To the 95th anniversary of Yevgeny Fedorovich Shnyukov - В.І. Старостенко; В.П. Коболев; О.А. Щипцов; С.В. Гошовський; В.В. Янко (Геофизический журнал, 2025)
March 26, 2025 is a significant date, the 95th anniversary of the birth of a dear and close person to us - Yevgeny Fedorovych Shnyukov (1930-2022). More than two years have passed since he passed away, but the pain of irreparable loss does not subside to this day.